EP601 Pelvic and para-aortic versus pelvic lymphadenectomy in intermediate and high risk endometrial cancer: a systematic review and meta-analysis. (1st November 2019) - Petousis, S; Panagiotis, C; Margioula-Siarkou, C; Papanikolaou, A; Athanasiadis, A; Rodolakis, A; Vergote, I; Kalogiannidis, I
Abstract : Introduction/Background: As the extend of lymphadenectomy for endometrial cancer remains controversial, a systematic review and meta-analysis was performed to assess the impact of combined pelvic and para-aortic lymph node dissection (PPALND) compared to only pelvic lymph node dissection (PLND) on survival outcomes of intermediate and/or high-risk patients. Methodology: Databases were searched up to 20 April 2018. Primary outcomes were overall survival (OS) and disease free survival (DFS). Secondary outcomes were the need for radiotherapy/chemotherapy/combined/adjuvant therapy, pelvic, para-aortic, intra-pelvic and extra-pelvic node recurrence, time to recurrence, pelvic, para-aortic and any node invasion rate at surgery. Pooled risk ratios were calculated using random effects models. Risk of bias of individual studies was assessed using the ROBINS-I tool. PROSPERO's registration number is CRD42017072337. Results: 13 studies were identified with 7349 patients. PPALND was associated with 46% decreased risk for death (HR: 0·54, 95% CI: 0·35–0·83) and increased 5-year DFS rate (RR: 1·13, 95% CI: 1·04–1·23). Furthermore, PPALND was associated with 49% decreased risk for recurrence (HR: 0·51, 95% CI:0·28–0·93), decreased need for radiotherapy (RR: 0·69, 95% CI:0·52–0·92), while increased risk for chemotherapy (RR: 1·71, 95% CI:1·36–2·14) was observed in the present study. There was no significant difference for adjuvant (RR: 0·98, 95% CI: 0·87–1·10) or combined therapy (RR: 1·45, 95% CI: 0·75–2·78). Para-aortic recurrence rate was higher for patients with only PLND (9·1% vs 5·2%), however with no significant difference (RR: 0·32, 95% CI: 0·04–2·55). There was limited evidence for intra-pelvic, extra-pelvic, pelvic node recurrence and time to recurrence. Risk of bias was critical or serious for all studies. Conclusion: There is low-quality evidence that PPALND contributes to improved survival outcomes in women with intermediate/high-risk endometrial cancer. Disclosure: Nothing to disclose.